Strategi Pembelajaran Guru Kelas IV Dalam Membantu Siswa Lamban Belajar Di SDK Golo Momol - Marselina Merni; Heronimus E. A. Wejang; Erna Mena Niman (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The problem in this study is that teachers have not optimally implemented individual learning strategies for slow learner students. This study aims to describe the learning strategies used by fourth-grade teachers in assisting slow learner students at SDK Golo Momol and to identify the inhibiting factors in the learning process for these students.This study used a qualitative research approach with a descriptive method. The subjects of this study consisted of the fourth-grade teacher and six fourth-grade students at SDK Golo Momol who experienced slow learning. The methods used for data collection were observation, interviews, and documentation. The data analysis techniques used in this study were data reduction, data presentation, and conclusion drawing.strategies used by the teacher in assisting slow learner students include adaptive learning strategies, individual learning strategies, repetition strategies, concrete or contextual learning strategies, motivational strategies, and multisensory learning strategies; (2) the inhibiting factors in the learning process include low student concentration, slow understanding of the material, limited teacher time for assistance, limited learning facilities and infrastructure, a relatively large number of students in the classroom, and a less conducive learning environment.Based on the results of the study, it can be concluded that the learning strategies implemented by the fourth-grade teacher in assisting slow learner students have been carried out through various approaches tailored to students’ needs. However, their implementation has not been optimal due to various inhibiting factors. Therefore, it is necessary to develop more effective and sustainable learning strategies to improve the quality of learning and the learning outcomes of slow learner students This study is important because slow learners require learning services that are tailored to their characteristics and needs. The lack of appropriate learning strategies can lead to difficulties in understanding learning materials and low academic achievement. In addition, studies specifically examining teachers' learning strategies in assisting slow learners at SDK Golo Momol are still limited. Therefore, this study is expected to contribute to the development of more effective and inclusive learning practices.